Airway allergy causes alveolar macrophage death, profound alveolar disorganization and surfactant dysfunction - Feo-Lucas, Lidia; Godio, Cristina; Minguito de la Escalera, María; Alvarez-Ladrón, Natalia; Villarrubia, Laura H.; Vega-Pérez, Adrián; González-Cintado, Leticia; Domínguez-Andrés, Jorge; García-Fojeda, Belén; Montero-Fernández, Carlos; Casals, Cristina; Autilio, Chiara; et al. (Frontiers in Immunology, 2023)
Respiratory disorders caused by allergy have been associated to bronchiolar inflammation leading to life-threatening airway narrowing. However, whether airway allergy causes alveolar dysfunction contributing to the pathology of allergic asthma remains unaddressed. To explore whether airway allergy causes alveolar dysfunction that might contribute to the pathology of allergic asthma, alveolar structural and functional alterations were analysed during house dust mite-induced airway allergy in mice, by flow cytometry, light and electron microscopy, monocyte transfer experiments, assessment of intra-alveolarly-located cells, analysis of alveolar macrophage regeneration in Cx3cr1cre:R26-yfp chimeras, analysis of surfactant-associated proteins, and study of lung surfactant biophysical properties by captive bubble surfactometry. Our results demonstrate that house dust mite allergy caused severe alveolar dysfunction, involving the death of alveolar macrophages, pneumocyte hypertrophy, thickening of alveolar lining and surfactant dysfunction. SP-B/C proteins were reduced in allergic lung surfactant, that displayed a decreased efficiency to form surface-active films able to reach and maintain low surface tensions, increasing the risk of atelectasis. Original alveolar macrophages were replaced by monocyte-derived alveolar macrophages, that persisted long after the resolution of allergy. Monocyte to alveolar macrophage transition occurred through an intermediate pre-alveolar macrophage stage and was concomitant with translocation into the alveolar space, Siglec-F upregulation, and CX3CR1 downregulation. These data support that the severe respiratory disorders caused by asthmatic reactions not only result from bronchiolar inflammation, but additionally from alveolar dysfunction compromising an efficient gas exchange.